harmonization and divergence in addressing the crime of drug possession and psychotropic substance use between the central government of Baghdad and the regional authorities. - Muhammad, Sheelan Salam; Ghafoor, Kosar Saeed (Journal of Legal and Political Studies, 2025)
This research aims to study the legislations regulating the crime of drug possession and use in Iraq, with a focus on the differences between the Iraqi Federal Law on drugs and psychotropic substances No. 50 of 2017 and the Kurdistan Region of Iraq’s drug control and psychotropic substances law No. 1 of 2020. The study focuses on differences in legal provisions related to the determination of penalties, criminal procedures, investigation mechanisms, and coordination between relevant institutions in the center and the region. The research examines the differences between Baghdad central government and the government of the Kurdistan region in legislative and regulatory aspects, such as the allowance of controlled delivery methods, retroactive application of the law, penalties, appeals against decisions issued by the competent minister, and the impact of these differences on achieving criminal justice and the effectiveness of combating drug-related crimes and unifying legal standards. The study adopts a comparative analytical approach to examine the laws and interpret their impact on anti-drug policies. It can be said that the disparity between the two laws reflects political and administrative differences between the central government and Kurdistan region. Focusing on regional legislations provides the region with flexibility in addressing drug issues in a manner that suits its needs, but this may lead to challenges in coordination with the central government, especially in cross-border cases. These cross-border challenges refer to the legal and procedural difficulties that may arise when dealing with drug cases that extend their effects or parties between two regions governed by different laws, namely between the Iraqi central government and the Kurdistan Region of Iraq. The research also proposes ways to achieve harmonization between the two legal systems, ensuring unified national efforts in combating drugs, while considering the region's particularities and legislative commitments. This research contributes to providing legal recommendations that enhance the integration of legislative and procedural policies between the center and the region, positively reflecting on national security and society. Keywords: Legislative Disparity, Drug Possession, Criminal Justice, Controlled Delivery, Crimes Involving Moral Turpitude.
Keywords: Legislative Disparity; Drug Possession; Criminal Justice; Controlled Delivery; Crimes Involving Moral Turpitude